Graphene nanoribbons as prospective field emitter - Khare, Ruchita T.; Shinde, Dhanraj B.; Bansode, Sanjeewani; More, Mahendra A.; Majumder, Mainak; Pillai, Vijayamohanan K.; Late, Dattatray J. (Applied Physics Letters, 2015)
Field emission characteristics of graphene nanoribbons (GNRs) synthesized by unzipping of multiwall carbon nanotubes using a facile hydrothermal route have been investigated at a base pressure of 1 x 10(-8) mbar. The values of turn-on field, required to draw an emission current densities of 1 and 10 mu A/cm(2), are found to be 2.8 and 5.8 V/mu m, respectively, and a maximum emission current density of 500 mu A/cm(2) has been drawn at an applied field of 9.8 V/mu m. The emission current stability of the GNRs emitter was studied at preset values of 1 and 10 mu A over a period of 3 h, and is found to be excellent. The field emission results demonstrated herein suggest that GNRs based field emitters can open up many opportunities for their potential utilization as large area field emitters in various vacuum micro-nanoelectronic devices such as flexible field emission displays, portable X-ray, and microwave tubes. (C) 2015 AIP Publishing LLC.

Glucose sensing and low-threshold field emission from MnCo2O4 nanosheets - Naik, Kusha Kumar; Khare, Ruchita T.; More, Mahendra A.; Late, Dattatray J.; Rout, Chandra Sekhar (RSC Advances, 2016)
Manganese cobalt oxide (MnCo2O4) nanosheets were grown on nickel (Ni) foam by a simple electrodeposition method. The as-synthesized nanosheets were characterized using X-ray diffraction and scanning electron microscopy. The Ni foam supports the growth of MnCo2O4 nanosheets without any aggregation, thereby increasing its catalytic and electronic properties. The electrochemical studies show that MnCo2O4 exhibits excellent electrocatalytic activity towards glucose sensing applications. The MnCo2O4 based glucose sensor shows a good sensitivity value of 8.2 mA mM(-1) cm(-2), with a response time of 19 s. In addition to this, field emission studies of as-synthesized MnCo2O4 reveal a low turn-on field value of 1.9 V mm(-1) and good emission current stability, demonstrating MnCo2O4 nanosheets as a good field emitter material.

Graphene nanosheets assisted carbon hollow cylinder for high-performance field emission applications - Tripathi, Prashant; Gupta, Bipin Kumar; Bankar, Prashant K.; More, Mahendra A.; Late, Dattatray J.; Srivastava, Onkar Nath (Materials Research Express, 2019)
Electron sources are critical constituents for myriad many electronic applications including electron imaging, mass spectroscopy etc. Here, we report the realization of high-performance field emission from graphene assisted carbon hollow cylinders (Gr-CHCs) composed of multi-stacked radially aligned CNTs. These CHCs have built-in synthesis related Fe nanoparticles (NPs). This engineered nano-structure exhibits excellent field emission properties such as one of the ultra-low turn-on field (0.64V mu m(-1) at 10 mu A cm(-2)), low threshold field (0.74V mu m(-1) at 100 mu A cm(-2)), very high current density (15.49 mA cm(-2) at 1.32V mu m(-1)) which is nearly double the current density obtained in our previous study. High field enhancement factor (0.72. x. 10(4)) with highly stable emission current at 100 mu A was observed for more than 3 hrs at the base pressure of similar to 1. x. 10(-8) mbar. This study suggests an approach to enhance the current density using the proposed innovative nanostructure and forms the basic theme of this communication. Highly efficient and stable field emissions observed are attributed to the geometry of cylinder and the production of the high density of sharp protrusions within the graphene sheets which enhance the local electric field and dramatically enhance field emission. This innovative cylindrical geometry associated with graphene assisted on Fe bearing aligned CNTs along with the periphery of the bulk cylinder provides an easy injection of electrons from the conduction band of CHCs into the vacuum in the presence of an external electric field. The tunability of field emission properties of these CHCs can be easily achieved by tailoring their diameter (10 and 20 mm) and different concentrations of the precursor. This new approach of the graphene assisted cylindrical geometry-based field emitter source provides enormous prospects and demand for next-generation high resolutions display devices.
Keywords: Carbon nanotubes; field emission; graphene assisted carbon hollow cylinder; protrusions